Loki zupa alleviates inflammatory and fibrotic responses in cigarette smoke induced rat model of chronic obstructive pulmonary disease - Nabijan Mohammadtursun; Qiuping Li; Muhammadjan Abuduwaki; Shan Jiang; Hu Zhang; Jing Sun; Jingcheng Dong (BMC, 2020)
Abstract Background Loki zupa formula is kind of a traditional medicines which used to treat airway diseases, especially those caused by abnormal phlegm, such as cough, asthma and chronic bronchitis. The study aim was to explore the anti-inflammatory and anti-remodeling effects of Loki zupa by using a cigarette-smoke induced rat model of chronic obstructive pulmonary disease. Methods The rats were divided into five groups: the normal group, the model group, the LZ 4 g/kg and LZ8g/kg group, and the positive control group. Rats were exposed to cigarette smoke for 24 weeks to induce a COPD rat model. Lung function was assessed. Histopathological changes were recorded using Haematoxylin-eosin and Masson's trichrome staining. Mucus hypersecretion was evaluated by PAS staining. Inflammatory factors were measured in blood serum and bronchial alveolar lavage fluid using an enzyme-linked immunosorbent assay. Malondialdehyde and superoxide dismutase and glutathione S-transferase levels were tested by biochemical methods. Gene expression patterns were evaluated using GN-GeneChip Clariom S Array for rat from Affymetrix. And top upregulated and downregulated genes validated by qPCR. And these genes was also compared with gene transcriptomic data from smoker patients with emphysema and non-smokers in GEO dataset. IL-6/PLAGA2A signalling protein expression was assessed by western blot and immunohistochemistry. TGF-β1and smad2/3 signalling expressions were analysed by western Blot. Results Loki zupa improved COPD rats lung function as compared to the model group and pathological changes including inflammatory cell infiltration and goblet cell metaplasia was alleviated in rats treated with Loki zupa Inflammatory factors IL-6, TNF-α, IL-1β and TGF-β1 decreased while significant increase was observed in blood serum IL-10 content in rats treated with Loki zupa. And IL-6 and TNF-α level in bronchial alveolar lavage fluid showed same expression trend in blood serum, while there was no change in MMP-9 content. It also increased antioxidant enzyme SOD and GPX activity while reducing the lipid peroxidation. Gene microarray analysis showed that there were 355 differentially expressed gene in LZ treated COPD rat lung as compared to model group. Both microarray and qPCR results showed that top differentially expressed genes nxt1 (up regulated) and pla2g2a (down regulated) expression were also reversed by LZ treatment. And protein expression level of IL-6 and pla2g2a was also elevated in CS exposed rats while significant reduction was observed in LZ treated rats. Accordingly, Loki zupa inhibited Collagen-1 upstream protein expression of TGF-β/smad2/3 signalling pathway. Conclusion These results demonstrated that Loki zupa showed protective effects in the lung of the COPD rat model. This mainly because of Loki zupa exerts anti-inflammatory effects by blocking IL-6/pla2g2a signalling and inhibiting inflammatory gene expression and attenuates fibrotic responses by inhibiting TGF-β/smad2/3 signalling pathway.